Consumer Decision Support System in Online Shopping in Market Place - Sefrika, S (IJISTECH (International Journal of Information System and Technology), 2024)
Online shopping transactions are common in today's society. Many people have changed their conventional shopping methods to online modes, so research needs to be conducted to find out what supports consumer decisions in making online shopping transactions through the market place platform. The research method uses TOPSIS, a multi-criteria method that offers an easier and more effective way to find out how or what underlies someone in determining certain decisions. TOPSIS is used to determine the preference value and distance of positive and negative ideal solutions as offered in the study. The results show that free shipping is the main reason for a consumer to make online transactions and fashion products are the most purchased items in online transactions.